2021
DOI: 10.3389/fpsyg.2021.754115
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Programs for Children and Adolescents: A Systematic Review and Meta-Analysis

Abstract: Resilience may be defined as the ability to recover and adapt to adverse situations. Given that resilience involves cognitive and behavioral aspects, it could be promoted based on strategies that favor them, especially during childhood and adolescence. As a result, several resilience-focused programs have been developed and studied. This systematic review of Randomized Controlled Trials (RCTs) aimed to assess resilience-focused programs for children (<12 years old) and adolescents (12–22 years old) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Another important criterion for successful coaching implementation was an interactive, gami ed design of the sessions. Some studies have demonstrated similar results for resilience coachings, but mainly focus on the experiences of healthy children (7,39).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Another important criterion for successful coaching implementation was an interactive, gami ed design of the sessions. Some studies have demonstrated similar results for resilience coachings, but mainly focus on the experiences of healthy children (7,39).…”
Section: Discussionmentioning
confidence: 83%
“…55 adolescents aged 12 to 16 years with CMC were recruited. Participants were included if (1) aged between 12 and 16 years old (2) having a CMC de ned as having a disease for over a year, mandatory long-term medical care or a signi cant impairment of daily life routine, (3) adequate knowledge of German for app play and coaching participation(assessed by parents or treating clinician), (4) su cient physical and mental condition for study participation (assessed with Lansky score (30)), (5) access to an Internet-enabled smartphone, (6) a signed informed consent form by both parents and participant (7) and no prior history of psychiatric or psychological treatment in the last three months or longer than three months.…”
Section: Samplementioning
confidence: 99%
“…The present study is very powerful because: (1) the content validity of the intervention was determined by nine experts and two adolescents at risk from the multidisciplinary expert committee; (2) it will promote different factors related to resilience, such as emotional regulation strategies, social and communication skills, problem-solving and peer support, among others; all of them have been related with resilience and described in the literature ( Dray et al, 2017 ; Gartland et al, 2019 ; Pinto et al, 2021 ; Llistosella et al, 2022 ); (3) it is dealing with adolescence, a period when several biological and psychological factors can affect and modify the normal development of the individual ( Azpiazu Izaguirre et al, 2021 ). It is also a period to lay the foundation for well-being and foster positive development, including resilience ( Morrish et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pinto et al . [ 24 ] in a systematic review and meta-analysis of 13 randomized controlled trials (RCTs) on resilience programs in children and adolescents reported a moderate effect of the programs in promoting resilience among adolescent students (standard mean differences [SMD] = 0.48), and some of these effects were sustained during the 6-month follow-up period (SMD = 0.12, P = 0.02).…”
Section: School-based Resilience Building Programs: Insight and Effec...mentioning
confidence: 99%